Implementation of Law Number 11 of 2022 Regarding the Management of Regional Revenue and Expenditure Budget Grants (Study on the Central Sulawesi Indonesian National Sports Committee) - Armin Amiruddin; Muhammad Akbar; Muh. Yusuf Hasmin (Program Pascasarjana Universitas Muhammadiyah Palu, 2023)
Law Number 11 of 2022 concerning the National Sports System concerning Sports Funding Article 75 states that sports funding is a shared responsibility among the central government, regional governments and the community; the government and regional governments are required to allocate sports budgets through the State Revenue and Expenditure Budget and the Regional Revenue and Expenditure Budget. The aim of the study was to analyze the implementation of Law Number 11 of 2022 concerning the Management of KONI Central Sulawesi Province APBD Grants and the supporting and inhibiting factors for its implementation. This research is descriptive in nature, namely describing the reality that occurs regarding the gap between the law that should be (das Sollen) and the applicable law (das Sein) where das Sollen regarding government policies regarding sports funding managed by the KONI Central Sulawesi Province. The results of the study show that the implementation of Law Number 11 of 2022 which regulates the management of grants sourced from the regional budget by KONI of Central Sulawesi Province has not been fully implemented because the law is still new and still needs in-depth study. The inhibiting and supporting factors for the management of grant funds are the absence of law enforcement, the lack of supervision over the implementation of grant funds managed by certain institutions and the factors that support transparent and accountable management of grant funds which are directly controlled by province, districts and city government officials.